2020
DOI: 10.7150/ijms.47766
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional prediction of the microRNAs differentially expressed in a mouse model of concanavalin A-induced autoimmune hepatitis

Abstract: In order to investigate the altered expression of microRNAs (miRNAs) in the development of autoimmune hepatitis (AIH), the aberrantly expressed miRNAs in the concanavalin A (Con A)-induced AIH mouse model were identified for the first time with microarray in this study. A total of 49 miRNAs (31 up-and 18 down-regulated) were screened out, and the qRT-PCR validation results of 12 chosen miRNAs were consistent with the microarray data. Combined with the profiling of differently expressed mRNAs in the same model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Because more and more evidence has proved that circRNAs regulate the function of miRNAs acting as the ceRNAs [49–51], circRNA–miRNA coexpression networks were constructed to predict the relationships between DECs and the differentially expressed miRNAs in the same model [26]. Eight DECs and 43 target miRNAs were involved in the established circRNA–miRNA coexpression network (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because more and more evidence has proved that circRNAs regulate the function of miRNAs acting as the ceRNAs [49–51], circRNA–miRNA coexpression networks were constructed to predict the relationships between DECs and the differentially expressed miRNAs in the same model [26]. Eight DECs and 43 target miRNAs were involved in the established circRNA–miRNA coexpression network (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…From the established circRNA–miRNA and miRNA–mRNA interaction network in the same model [26], a latent circRNA–miRNA–mRNA network ‘ mmu_circ_0001520/mmu‐miR‐193b‐3p/MAPK10 ’ was constructed, and it was suggested that this predicted network was likely to be associated with the occurrence and development of AIH based on the literature research. Although no functional annotations of mmu_circ_0001520 have been presented, complement component 1, s subcomponent 1, the best transcript of this DEC, was annotated in the GO terms of ‘complement activation, lectin pathway’ (GO:0001867) in the BP category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, high-throughput detection techniques on screening the differentially expressed genes (involving the coding RNA and non-coding RNA) can be applied to this model, just like the research we are doing, to further explain the interaction between signal transduction pathways [ 61 , 89 , 90 ]. In particular, much more attention should be paid to the differentially expressed genes enriched in signaling pathways associated with T cell activation and NF-κB transcription.…”
Section: Application Prospect and Possible Improvementsmentioning
confidence: 99%
“…Auto-immune hepatitis (AIH) is considered immune disorder-induced hepatic injury mediated by abnormal activation of immunocytes and production of proinflammatory mediators [11]. Concanavalin A-(Con A-) induced hepatitis has similar histopathological features and is widely used to establish AIH models in studies [12,13]. Con A can activate the Kupffer cells (KCs) and promote them to secrete proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), thus aggravating the inflammatory response and eventually causing hepatic damage [14,15].…”
Section: Introductionmentioning
confidence: 99%